2019
DOI: 10.18332/ejm/112258
|View full text |Cite
|
Sign up to set email alerts
|

Adult male involvement in maternity care in Enugu State, Nigeria: A cross-sectional study

Abstract: INTRODUCTION Men are the key decision makers in the family and play a crucial role in the reproductive health of partners, in Nigeria. This study assessed adult male involvement in maternity care in Enugu south local government area, Enugu State, Nigeria. METHODS This community-based study was conducted using a cross-sectional survey design. A total of 145 respondents were selected through multi-stage sampling and data were collected using a structured questionnaire developed by the researchers. Data generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Poor spousal communication was an impeder to planning for maternal health services in Ghana [15]. Male partners involvement in antenatal care was still below the World Health Organisation threshold [16]- [19]. The weakness of these studies in Sub-Saharan Africa investigated only antenatal care and left skilled birth services.…”
Section: Introductionmentioning
confidence: 99%
“…Poor spousal communication was an impeder to planning for maternal health services in Ghana [15]. Male partners involvement in antenatal care was still below the World Health Organisation threshold [16]- [19]. The weakness of these studies in Sub-Saharan Africa investigated only antenatal care and left skilled birth services.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was determined based on the sample size formula for cross-sectional studies in populations greater than 10,000 stated thus [25]: n=Z 2 pq/ d 2 , where n= minimum sample size; Z=Standard normal deviate set at 1.96 (95% confidence interval); p = prevalence of male involvement in maternal health. Mbadugha, et al, reported 39% of respondents who reminds their partners of her medications, antenatal visits and other examinations in Achara Enugu South LGA of Enugu State, [18], while q=1-p, i.e. p=0.39 and q=0.61, with d = Maximum allowable error (5% = 0.05) [25].…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…Here, fathers and other males in the community facilitate access to better healthcare facilities and services for women and girls [14,15]. A male is involved if he is present, accessible, available, understanding, willing to learn about the pregnancy process and willing to provide emotional, physical and financial support to the woman carrying the child [16][17][18]. However, there remains a wide gap between male partner involvement policies and the actual involvement in maternal health [18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, educational and economic disparities can play a critical role in shaping men's involvement in pregnancy care as men with higher levels of education and income may have more resources and ability to participate actively ( 7 , 11 ). Also, men's own perceptions and expectations about their roles during pregnancy and the prevailing socio-cultural norms and stereotypes that delineate roles across gender divides can influence participation as many cultures typically feminize activities relating to pregnancy and childbirth ( 8 , 12 , 19 , 20 ). Unhospitable attitude of maternity care staff, exclusion of men from obstetric care activities and unconducive facility environment may have negative impact on men's level of engagement ( 10 , 14 , 21 ).…”
Section: Introductionmentioning
confidence: 99%